"Beauty and the Helldivers": Representing Women's Work and Identities in a Warplant Newspaper - Smith, Helen; Wakewich, Pamela (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1999)
In this article, we discuss representations of women's identities as workers in the wartime newspaper, Aircrafter, produced by management at the Canadian Car and Foundry Company Limited in Fort William, Ontario, during World War II. We argue that Aircrafter functioned as an ideological mechanism by which pre-war, middle-class prescriptions of femininity, emphasizing women's roles as decorative homemakers in the private sphere, survived the challenges of women's war work to shape post-war gender roles. The article demonstrates the efficacy of this ideological mechanism by revealing the comprehensive way in which different rhetorical styles and varied sections of the newspaper — the front page news and pictures, the editorial page, the women's page entitled "The Feminine Touch," as well as cartoons and pin-ups — collectively conveyed an ambivalent attitude that both praised and questioned women's war work in traditionally male jobs thus reinforcing pre-war socially prescribed forms of femininity. This research reveals how state policies concerning representations of women workers in government war propaganda influenced a northwestern Ontario war plant and shaped the ideological atmosphere which the women war workers at Canadian Car would have to negotiate as part of their daily working lives.